Time management strategy and its impact on reducing the causes of job stress: An exploratory study of the opinions of a sample of Tikrit University employees (Journal of Humanities and Social Sciences Research, 2023)
This study seeks to determine the effect of time management strategy in reducing the causes of job stress in the organization under investigation. The study adopted the descriptive analytical approach to deal with theoretical propositions and practical data and attempt to harness them to achieve the objectives of the current study. The study population reached (80) individuals from unit and division officials in the colleges of (Administration and Economics, Education for Pure Sciences, Engineering, Science, Agriculture and the College of Law). The data collection tool was the questionnaire and it was distributed to a sample of (65) questionnaires. The study came out with a set of conclusions, the most important of which are: The time management strategy includes conscious awareness of the art of using time, and knowledge of ways to exploit it in a practical and effective manner, in order to raise individuals’ performance rates and increase productivity. The study presented a set of recommendations in light of the conclusions drawn, the most important of which were: identifying time management strategies in a way that reduces procrastination, reduces interruptions, and enhances discipline, especially when engaging in organizational activities.